Rancang Bangun Sistem Monitoring Cuaca Low Power Berbasis Mikrokontroler - Heri Setiawan; Rakhmadhany Primananda; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Paragliding is one of the flying sports that is currently experiencing an increase in the number of pilots and many locations are provided. To monitor the safety of paragliding take-off an instrument for energy-efficient weather monitoring is needed so that the system can work more efficiently at a paragliding take-off location far from electric power sources. This weather monitoring instrument consists of 2 sensor nodes, sensor node 1 for weather monitoring and as a system that applies the duty cycle method for power savings consisting of sensors temperature, humidity, altitude, rain conditions, wind speed and wind direction. Sensor node 2 for monitoring current and voltage flowing on sensor node 1 and as the sender of sensing data to thingspeak. The results of the acquisition of the weather monitoring system sensor module have an average sensing accuracy above 85%. The results of the percentage testing of the effectiveness of saving current consumption from sensor node 1 obtained a saving value of 28.87%.